KESESUAIAN PENYEDIAAN INFRASTRUKTUR PADA PENGEMBANGAN KORIDOR EKONOMI INDONESIA - IGW Samsi Gunarta; Wimpy Santosa; Anastasia Caroline Sutandi (Jurnal HPJI (Himpunan Pengembangan Jalan Indonesia), 2021)
Abstract The Indonesian Economic Corridor is 1 of the 3 pillars in the Master Plan for the Acceleration and Expansion of Indonesia's Economic Development 2011–2025. This initiative applies the concept of a modern corridor, which divides Indonesia's territory into 6 economic corridors, according to the competitive advantages of each region. This study aims to compare whether the infrastructure planned and built by the Government for each economic corridor is in-line with the expectations of the people who live in that economic corridor. In this study, a survey was conducted to determine the public's perception of the infrastructure needed for the development of an economic corridor. The results are then compared with the infrastructure provision plan that has been and will be developed by the Government. The study shows that there are differences between the infrastructure provided by the Government and those needed by the people in each corridor. Kalimantan Corridor shows the best proportion of supply-demand suitability which provided 3 out of 5 required infrastructures.Overall, there are infrastructures, which are commonly needed to ensure the growth of economic corridor, namely a well-connected transportation backbone, availability of alternative transportation modes and their inter-modal facility, ports with good services, and the availability of high-speed internet networks. Corridors that can be selected as a model for corridor development are the Java and the Bali-NTB-NTT Corridors, because these corridors have a high number of infrastructure suitability and have all the infrastructure needed by each corri-dor. Keywords: economic corridor; infrastructure; infrastructure provision; infrastructure needs; public perception.  Abstrak Koridor Ekonomi Indonesia adalah 1 dari 3 pilar dalam Masterplan Percepatan dan Perluasan Pembangunan Ekonomi Indonesia 2011–2025. Prakarsa ini menerapkan konsep koridor modern, yang membagi wilayah Indonesia menjadi 6 koridor ekonomi, sesuai dengan keunggulan masing-masing wilayahnya. Penelitian ini bertujuan untuk membandingkan apakah infrastruktur yang direncanakan dan dibangun oleh pemerintah untuk setiap koridor ekonomi sesuai dengan harapan oleh masyarakat yang ada di koridor ekonomi tersebut. Pada penelitian ini dilakukan survei untuk mengetahui persepsi masyarakat tentang infrasruktur yang dibutuhkan untuk pengembangan suatu koridor ekonomi. Hasil survei ini selanjutnya dibandingkan dengan rencana penyediaan infrastruktur yang telah dan akan dikembangkan oleh pemerintah. Hasil studi ini menunjukkan bahwa terdapat perbedaan antara infrastruktur yang direncanakan oleh pemerintah dan yang dibutuhkan oleh masyarakat di setiap koridor. Proporsi kesesuaian antara pasokan dan permintaan terbaik terdapat di Koridor Kalimantan, yang mendapatkan pasokan pemerintah berupa 3 dari 5 infrastruktur yang dibutuhkan. Secara keseluruhan, terdapat kesamaan infrastruktur yang benar-benar diperlukan untuk pengembangan suatu koridor ekonomi, yaitu backbone transportasi yang terkoneksi baik, ketersediaan moda transportasi alternatif beserta fasilitas integrasinya, pelabuhan dengan pelayanan yang baik, serta ketersediaan jaringan internet dengan kecepatan tinggi. Koridor yang dapat dipilih sebagai model pengembangan koridor adalah Koridor Jawa dan Koridor Bali-NTB-NTT, karena memiliki jumlah kesesuaian infrastruktur yang tinggi dan memiliki seluruh infrastruktur yang sangat dibutuhkan oleh setiap koridor. Kata-kata kunci: koridor ekonomi; infrastruktur; penyediaan infrastruktur; kebutuhan infrastruktur; persepsi masyarakat.KESESUAIAN PENYEDIAAN INFRASTRUKTUR PADA PENGEMBANGAN KORIDOR EKONOMI INDONESIA